Riñón en T: anomalía congénita rara de fusión renal - Wert Alvarez, Carlos Manuel; Gómez Garlobo, Manuel; Hernández Cabrera, Lisabeth; Correa Acuña, Dra. Yunia; Alvarez Peña, Dra. Mayra M.; Bell Duconger, Dra. Esmeralda (Revista 16 de abril, 2015)
Se presenta el hallazgo anatomopatológico de un caso de fusión renal no descrita en la literatura; en un paciente masculino de 52 años de edad sin antecedentes conocidos de enfermedades del aparato urinario. ABSTRACT The present paper shows up the anatomopatologycal discovery in a 52 year-old masculine patient without well-known antecedents of illnesses of the apparatus urinary deceased extrahospitalary. The result of the autopsy evidenced the presence of a case of renal coalition in T, not described in the literature.